Effect of Germination Media and Planting Depth on Viability and Vigor of Rubber Seed (Hevea brasiliensis Muel.Arg) - Fahrizal (Central Research Institute For Agriculture, 2022)
This study aims to determine the effect of germination media and planting depth on viability and vigor of rubber seeds and whether or not the interaction between these two factors is significant. It was held in Gampong Kuta Padang, Johan Pahlawan District, West Aceh Regency, on February 14 to March 30, 2013. The seeds used in this study were local varieties of rubber seeds that had been selected as many as 675 seeds obtained from community gardens in East Seunagan District, Nagan Raya Regency. . This study used a completely randomized design (CRD) with 3x3 factorial pattern with 3 replications. There are 2 factors studied, namely germination media and planting depth. The germination media factor consisted of three levels, namely soil: sand, soil: compost, and soil: sawdust. The planting depth factor consists of three levels, namely 1, 2, and 3 cm. The observed variables included growth potential, germination capacity, growth speed, growth synchronously and germination vigor. The results showed that sprout media had a significant effect on growth potential, germination capacity, growth speed, sprout vigor and had no significant effect on growth simultaneously. The best viability and vigor of rubber seeds were found in soil germination media: compost. Planting depth had a significant effect on all observed variables. The best viability and vigor of rubber seeds were found at a planting depth of 2 cm. There was no significant interaction between germination media and planting depth on all variables of viability and vigor of rubber seeds observed.